Endoscopic para-thyroidectomy: a new approach - Aziz, MM; Khan, AW; Uddin, MF; Hasanat, MA; Kader, MA; Chowdhury, AJ; Choudhury, NA (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):442-6 The abstract of this article is available on the PubMed website